Traversing boundaries a situated music approach to the study of day-eng performance among the Kankana-ey of Northern Philippines - Dela Pena, La Verne David C.
"This dissertation examines day-eng as situated music--specific instances of musical performance tied to authentic human situations. The appraoch shifts the locus of the ethnomusicological inquiry from places and groups of peoples, or geo-political areas, to happenings or particular episodes in the life of a community."